2010
DOI: 10.2478/s11756-010-0073-z
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of epibenthic community in the inshore waters of southeast coast of India

Abstract: The epifaunal assemblage was evaluated at three different depths (5, 15 and 25 m) in the inshore waters of Pazhayar, Parangipettai and Cuddalore apart from 5 m depth near SIPCOT covering totally 10 stations (11• 21 N to 11• 42 N; 79• 46 49 E to 79• 52 34 E) in the southeast coast of India, Bay of Bengal. The occurrence of as many as 112 species belonging to 6 groups was recorded. Among these, gastropods constituted the largest component (42.85%) with 48 species. Bivalves came next with the percentage contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A few studies focused on the economically important bivalve species and associated conservation efforts (Rao, 1974; Kripa & Appukuttan, 2003). Various other studies reported overall diversity of organisms including bivalves from localities in the southern coast (Kurian, 1971; Khan et al , 2010; Kundu et al , 2010; Manokaran et al , 2015), east coast (Ansari et al , 1977; Mahapatro et al , 2011), and west coast (Parulekar, 1973; Parulekar & Dwivedi, 1974; Parulekar & Wagh, 1975; Jayaraj et al , 2007). Such studies conducted at a local scale, although common, may be limited in their utility in explaining larger patterns.…”
Section: Discussionmentioning
confidence: 98%
“…A few studies focused on the economically important bivalve species and associated conservation efforts (Rao, 1974; Kripa & Appukuttan, 2003). Various other studies reported overall diversity of organisms including bivalves from localities in the southern coast (Kurian, 1971; Khan et al , 2010; Kundu et al , 2010; Manokaran et al , 2015), east coast (Ansari et al , 1977; Mahapatro et al , 2011), and west coast (Parulekar, 1973; Parulekar & Dwivedi, 1974; Parulekar & Wagh, 1975; Jayaraj et al , 2007). Such studies conducted at a local scale, although common, may be limited in their utility in explaining larger patterns.…”
Section: Discussionmentioning
confidence: 98%
“…Industrial development along the Parangipettai coasts has rapidly expanded in recent years and substantial growth is planned for the near future (Kanakaraj et al 2003;Ajmal Khan et al 2010). Therefore, the present investigation was undertaken to describe meiobenthic communities with a special emphasis on free-living marine nematode diversity and community structuring from the continental shelf off Parangipettai (Bay of Bengal), which will serve as a baseline of information for assessing benthic diversity trends across South Asian continental shelfs.…”
Section: Introductionmentioning
confidence: 99%
“…This may be the reason for the low abundance of amphipods here. Previous study done (AjmalKhan et al, 2010) in Cuddalore-Parangipettai area on the epifauna showed low number of species in the SIPCOT region which was indicative of the stress here. Due to stress, Simpson dominance index was found high and other diversity indices (Shannon, Margalef etc.)…”
mentioning
confidence: 51%